Impact of Extended Intervals on Diesel Engine Performance with 15W-40 DH1 Lubricant Oil - Wiwit Suprihatiningsih; Arief Priyanto; Nurato Nurato; Arief Suardi Nur Chairat; Denny Prumanto (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2024)
Engine lubricant oil is crucial for minimizing friction between moving components within an engine, directly influencing the engine's reliability and lifespan. Determining the appropriate oil replacement intervals is essential, as extending these intervals necessitates more rigorous monitoring of both oil quality and engine condition. This study investigated the performance of SAKAI 15W-40 DH1 engine oil in the SAKAI Vibrating Roller SV526 over varying operational periods: 125 hours, 250 hours, 375 hours, and 500 hours. The research involved analyzing oil samples for viscosity, metal additives, total base number (TBN), and contaminants using Fourier Transform Infrared Spectroscopy (FTIR). Additionally, key engine performance indicators, including fuel consumption, valve clearance, and compression pressure, were measured. The findings revealed a gradual decrease in oil viscosity from 13.48 cSt to 11.56 cSt, approaching the minimum acceptable threshold of 11.45 cSt. Concurrently, the Fe content in the oil increased to 11 ppm, indicating wear, while the valve clearance in cylinder number three expanded to 0.48 mm, and compression pressure dropped from 31 kg/cm² to 28 kg/cm². Despite these changes, the oil remained within the standard operational limits, and the engine continued to perform adequately. However, based on the observed trends, extending the oil replacement interval to 500 hours cannot be conclusively recommended, as the oil's condition and engine performance may begin to decline beyond this point.